Enhancing Students’ Critical Thinking through Case-Based Science Teaching Materials - Fembriani Fembriani; andriyani afliyanti dua lehan; Netty elisabeth antoneta Nawa (JURNAL PENDIDIKAN DASAR NUSANTARA, 2026)
This study aims to examine the effectiveness of science teaching materials developed using a case-based learning approach in enhancing critical thinking skills. The research employed an experimental method with a pretest–posttest control group design. The sample consisted of 66 first-semester students enrolled in the Elementary School Teacher Education Program at Nusa Cendana University. The findings revealed that the average posttest score of the control group was 59, while the experimental group achieved an average score of 87. The paired-sample t-test results for the posttest scores of the control and experimental groups yielded a significance value of 0.000, indicating a statistically significant difference between the two groups. Furthermore, student responses to the implementation of the teaching materials reached 94%. These results indicate that the use of case-based learning–oriented science teaching materials is effective in improving critical thinking skills, with student responses categorized as very effective.